Competency-based practice in conducting natural science research and presenting its results in primary classes: A case study - Jakavonytė-Staškuvienė, Daiva; Ponomariovienė, Jovita (Cogent education, 2023)
Competency-based education practice is a priority area, but there is limited scientific research analyzing the education process of holistically developing students' competencies and subject matter skills. The aim of the study is to provide scientific evidence for the integrated competency-based education practice of primary school students during the process of conducting natural science research and presenting the findings. The study involved 15 third-grade pupils (4 girls and 11 boys) from a private school in Lithuania, and two teachers who facilitated the class (a primary school teacher and an English language teacher). Convenience sampling was used. The article describes the detailed process of the study and the learning process of the students, reflecting on the intentional use of digital content in the learning process, when students sought the meanings of natural science concepts in both Lithuanian and English. The data were analyzed using a qualitative content thematic analysis, organized to the following clusters: interest in the activity, group work, information search, exploration and poster creation. In conclusion, it can be said that the students developed a learning culture in Lithuanian and English, reasoned and confidently shared their insights while seeking answers about different materials, their combustion properties. However, when faced with difficulty, even though they worked in a group, they first turned to the teacher for help rather than to their peers. The students have strong independent work skills, as they initiated the activity of improving the poster themselves. The development of communication culture in the education process not only allowed for the analysis of natural science content in Lithuanian and English, but also for the improvement of communication, social-emotional and digital competence skills.